Managing innovation : - Whittaker, D. H. (Cambridge University Press, 1990)
Innovation is a key to corporate success, particularly in times of rapid technological change. This book sheds new light on the introduction of technology in the manufacturing sector. The author considers the use of innovative technology in both Britain and Japan by examining nine firms in each country. He focuses on computerized machine tools (CNC) and shows how the various firms have risen to the challenge of implementing the new technology. Particular emphasis is placed on the differing employment relations in the factories, the nature of operator training and workload distribution. Dr. Whittaker identifies fundamentally different approaches in the two countries that have implications for competitiveness as well as future innovation. The contrast is especially interesting since Japanese industrial relations are commonly distinguished by their cooperative nature while industrial relations in Britain have tended to be more confrontational. These conventional views are challenged with an original perspective on the labor process and new technology. The book will be of major interest to specialists in technical innovation and industrial relations. Managers eager to learn the practical lessons of a comparison between British and Japanese work habits will also gain much from reading this book.